(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
The present article mainly focused on the ethnomedicinal plants used by the community living in and around Dhaka to manage the diabetes. Ethnomedicinal data were collected using semi-structured interviews with key informants during June 2017 to July 2018 followed by field interviews, plant interviews, checklist interviews and group discussion techniques. A total of 92 ethnomedicinal plant species under 46 families have been documented. These species were used to treat 55 ailments through 200 formularies. Herbs are the most common medicinal plants in the study area followed by trees, shrubs and climbers. Leaf is mostly used for the preparation of herbal medicine. Among the total 92 ethnomedicinal plants, 11 species have been used for diabetes management by the community people. Disease category diabetes showed maximum factor informant consensus value. Most cited ethnomedicinal plant species for the diabetes management are Gynura nepalensis DC., Coccinia grandis L. Voigt, Aloe vera (L.) Burm. f., Syzygium cumini (L.) Skeels, Swietenia mahagoni (L.) Jacq., Momordica dioica Roxb. ex. Willd., Catharanthus roseus (L.) G. Don, Streblus asper Lour., Bryophyllum pinnatum (Lamk.) Oken, Tamarindus indica L. and Scoparia dulcis L. The results in the present study for diabetes management were very preliminary and based on which sound conclusion was not possible. Further ethnopharmacological study is very essential on such species to validate their efficacy in the management of diabetes. Our findings also provide baseline data to establish a connection between the traditional users of medicinal plants and scientific communities, which can be substantial in novel drug discovery. Furthermore, ethnomedicinal data is of significant value for conservation managers and policy makers for sustainable management of ethnomedicinal plant species, which are under threat due to rapid urbanization.